Prospects for Achieving Sustainable Development Through the Millennium Development Goals in Nigeria. - Akintoye, Victor Adejumo; Opeyemi, Oluwabunmi Adejumo (European Journal of Sustainable Development, 2014)
In recent time, the concept of sustainable development cannot be overemphasized. Since the early 1980s, the term ‘sustainable development’ has been used widely and indiscriminately. The term began to gain popularity, when it became increasingly fashionable to use it as a way of responding to global environmental concerns, biophysical issues, fairness, equity and distribution. With this in mind, the Millennium Development Goals (MDGs) were put up in recent times to address and include the issue of sustainability in development. In essence, this study is carried out with a view to enhance the understanding about the analytical content of sustainable development as well as sensitizing the Nigerian economy to key into the current wave of sustaining the global economy. In the light of some of the environmental as well as socio-economic challenges permeating the Nigerian economy, it is therefore required that the Nigerian government concentrates on key areas that can help boost and sustain its developmental objectives. Hence, this paper helps to understand the concept and need for sustainable development. Besides, key developmental areas that require sustainability in Nigeria are addressed. Key Words: “Sustainable”, “Globalization”, “Environment”, “Development”